Zn-rich pyroxenes from the ore occurrences in the mixed series in the upper part of the Babuna River, Macedonia - Jančev, Simeon (Geologija, 1997)
The basic purpose of this report was the determination of very fine-grained (cca 0.02-0.05 mm) corroded Zn-rich pyroxenes relics that occur in the mineralized dolomite marbles and baryte schists. The determination was performed particularly by means of the electron microprobe analysis that established the new mineral varieties of Zn-rich aegirine-augite composition. The examined pyroxenes were confirmed as pyroxenes, and established by X-ray powder data inside of a complex polyphase mineral system consisting of Zn-rich pyroxenes, Zn-rich richterite, Zn-rich phologopite and baryte.